Diskursus Pertimbangan Hakim Terkait Studi Kejahatan Seksual Terhadap Pekerja Seks Komersial Anak - Fauzia Musdalifa Z. A. Nuna; Suwitno Yutye Imran; Jufriyanto Puluhulawa (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2024)
This research aims to determine and analyze the role and position of child victims in sexual crimes and legal protection efforts through victimology theory in normative decisions. Legal materials are collected through document study, then analyzed prescriptively. The research results found that there are regulations that have not been specifically regulated to protect children from all sexual crimes. Then, the role and position of the child victim which was not assessed as a consideration by the Judge in Decision Number 102/Pid.sus/2022/PN Lbo is something that hinders legal protection efforts for children. This research also contains victimology analysis of child victims using the Carroll Formula as well as other analyzes that show the victim's position as a commercial sex worker, which shows that there is a trigger for a crime. Victimology theory in decisions is important to understand the role of child victims who are considered passive perpetrators so that the theory of justice can be included in decisions and child protection through victimology theory can be implemented.